DETERMINATION OF THE INTENSITY AND DIRECTION OF THE TRANSIT TRAFFIC FLOWS IN CENTRAL BUSINESS DISTRICT - , Е. М., Д. В. (Municipal economy of cities. Series: «Economy science», 2013)
The question of determining the value of transit traffic in the central business district. Provided a method for calculating transport of correspondence passing through the central business district using a modified gravity model.